Iranian brown propolis possesses neuroprotective effect against ischemic neuronal damage in mice - Gholamreza Bazmandegan; Ali Shamsizadeh; Mohsen FathiNajafi; Zahra Assadollahi; Mohammad Allahtavakoli; Zahra Kamiab; Alireza Vakilian; Amir Moghadam-Ahmadi; Morteza Amirteimoury; Mohammad Taher Boroushaki (Shahrekord University of Medical Sciences, 2020)
Introduction: Stroke is one of the leading causes of death and disability worldwide. Propolis, a polyphenol-rich resinous product processed by honeybees from a variety of plant sources, has a set of biological activities. We investigated the neuroprotective effect of Iranian brown propolis (IBP) in a mouse model of permanent middle cerebral artery occlusion (MCAO). Methods: Experimentally, water extracts of propolis (WEPs) were obtained from Kerman (KeWEP) and Khorasan Razavi (KhWEP) provinces, Iran. The chemical characterization and total polyphenol content of WEPs were determined using the Folin-Ciocalteu assay and gas chromatography-mass spectrometry (GC-MS). Animals were divided into eight experimental groups including: sham, control, and three groups each of which KeWEP- and KhWEP-treated mice. The drugs were administered at doses of 30, 100 and 200 mg/kg, intraperitoneally (IP), during four different time points. Infarct volume and brain edema were measured at 48 h. Behavioral tests were evaluated at 4, 24 and 48-hour post stroke. Results: The total polyphenol content was 1100 and 1400 mg/L in KhWEP and KeWEP respectively. Compared to the control group, the doses of 100 and 200 mg/kg in both samples decreased infarct volume. Brain edema was also reduced in all treatment groups. The dose of 200 mg/kg in both samples and 100 mg/kg in the KeWEP-treated group significantly increased grasping ability. Sensory-motor function was improved in all groups, too. Conclusion: These results suggest that IBP may reduce ischemic brain injury by its neuroprotective effect on focal cerebral ischemia.